2012
DOI: 10.1007/s00128-012-0628-5
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and Bioaccumulation of Copper by the Entomopathogen Beauveria bassiana (Bals.-Criv.) Vuill. Exposed to Various Copper-Based Fungicides

Abstract: This work evaluates for the first time the relationships between copper-tolerance, -solubilization and -bioaccumulation in the entomopathogen Beauveria bassiana exposed to Bordeaux mixture, copper oxychloride or copper hydroxide. Bordeaux mixture was highly detrimental to fungus, by inhibiting the growth totally at the recommended dose (RD) and 2×RD. Copper hydroxide and copper oxychloride were found to be less toxic, reducing fungus growth, sporulation and conidial germination in an average of 29  %, 30 % and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 26 publications
(40 reference statements)
3
14
4
Order By: Relevance
“…In contrast, mycelial growth was found to be less affected by the fungicide. These results were in agreement with those previously reported for B. bassiana when exposed to non‐copper as well as to copper‐based fungicides, including Bordeaux mixture . Mycelial growth, sporulation and, especially, germination are important in insect infection and disease transmission.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In contrast, mycelial growth was found to be less affected by the fungicide. These results were in agreement with those previously reported for B. bassiana when exposed to non‐copper as well as to copper‐based fungicides, including Bordeaux mixture . Mycelial growth, sporulation and, especially, germination are important in insect infection and disease transmission.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies by the present authors showed that the addition of Bordeaux mixture to agar medium reduced significantly B. bassiana growth, sporulation and germination . This inhibitory effect was noticed throughout the incubation period (12 days).…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…Another concern in applying algicides to treat CyanoHABs is leaving harmful chemical residuals that cause secondary contamination (65). CuSO 4 is not only an algicide but also a fungicide and insecticide (66,67). Similarly, the function of tryptamine and tryptoline is much broader than lysing cyanobacteria.…”
Section: Discussionmentioning
confidence: 99%